Phonetic documentation in three collections: Topics and evolution. (28th April 2022) - Whalen, D. H.; DiCanio, Christian; Dockum, Rikker
Abstract : Phonetic aspects of many languages have been documented, though the breadth and focus of such documentation varies substantially. In this survey, phonetic aspects (here called 'categories') that are typically reported were assessed in three English-language collections – the Illustrations of the IPA from the Journal of the International Phonetic Association, articles from the Journal of Phonetics, and papers from the Ladefoged/Maddieson Sounds of the World's Languages (SOWL) documentation project. Categories were defined for consonants (e.g. Voice Onset Time (VOT) and frication spectrum; 10 in total), vowels (e.g. formants and duration; 7 in total) and suprasegmentals (e.g. stress and distinctive vowel length, 6 in total). The Illustrations, due to their brevity, had, on average, limited coverage of the selected categories (12% of the 23 categories). Journal of Phonetics articles were typically theoretically motivated, but 64 had sufficient measurements to count as phonetic documentation; these also covered 12% of the categories. The SOWL studies, designed to cover as much of the phonetic structure as feasible in an article-length treatment, achieved 41% coverage on average. Four book-length studies were also examined, with an average of 49% coverage. Phonetic properties of many language families have been studied, though Indo-European is still disproportionately represented. Physiological measures were excluded as being less common, and perceptual measures were excluded as being typically more theoretical. This preliminary study indicates that certain acoustic properties of languages are typically measured and may be considered as an impetus for later, fuller coverage, but broader consensus on the categories is needed. Current and future documentation efforts would benefit these considerations being addressed.